SrSnO3: Cu obtido pelo método dos precursores poliméricos, para a redução catalítica de NO com CO - Ribeiro, Danniely de Melo (2011)
Strontium stannate (SrSnO3) is a perovskita with orthorhombic structure (Pbnm), which has been extensively studied due to its potential technological applications, such as: thermally stable capacitors, sensors for various gases, including CO, NOx, Cl2, H2 and humidity. Nowadays, it has been studied as a promising material to be used as a catalyst. In this work, Sr1-xSnCuxO3, SrSn1-yCuyO3, Sr1-xSn1-yCux+yO3 (x, y ou x+y = 0; 1; 5 e 10% mol the copper) powders were synthesized by the polymeric precursor method and characterized by thermogravimetric analysis (TG/DTA), X-ray diffraction (XRD), infrared (IR) and ultraviolet-visible (UV-Vis) spectroscopy, Raman spectroscopy, specific surface area (BET) and then powders were evaluated in the catalytic reduction of NO with CO. The powders (SrSnO3:Cu) had orthorhombic perovskite structure at 700 oC, with SrCO3 and SnO2 as secondary phases. The introduction of copper in the structure leads to a higher short range disorder, as evidenced by the infrared and Raman spectra. In the Infrared spectra, the splitting of the 3 band (500-700 cm-1) was observed, which can be associated to the presence of two types of symmetry around the tin. In UV-Vis spectra bands related to d-d transitions of Cu2+ ions were observed besides related to forbiden transitions of Cu+ ions for higher calcination temperatures and copper amounts. The catalytic activities of SrSnO3 was improved by copper addition into the structure, whereas samples with 5 % of copper presented the highest conversions, reaching 100 % of NO into N2 and 100 % of CO into CO2 at 550 oC. This result is as good or even better than lanthanium based catalysts. The surface area was not a determining factor for NO reduction and CO oxidation. Other factors were more important for a high catalytic performance, as defects, that lead to more active sites for NO and CO adsorption, besides the presence of Cu+ and redox reaction (Cu+/Cu2+) that improve adsorption and NO reduction by CO.